Classification of White Cultivar Wines by Origin using Volatile Aroma Components - Marais, J.; Van Rooyen, P. C.; Du Plessis, C. S. (South African Journal of Enology and Viticulture, 2017)
Stepwise discriminant analysis was applied to gas chromatographic data of some volatile compounds obtmiieabjiTreonextracliOii"of dry white table wines. By means of this statistical method, successful classifications according to origin of Colombar wines from two regions, and Chenin blanc wines from three regions, were obtained. The components with the highest discriminatory value were i-amyl acetate, hexyl acetate and i-butanol, in the case of the Colombar wines and hexanol and 2-phenyl ethanol in the case of the Chenin blanc wines.